Effects of Ving Tsun Chinese Martial Art Training on Upper Extremity Muscle Strength and Eye-Hand Coordination in Community-Dwelling Middle-Aged and Older Adults: A Pilot Study. (20th July 2016) - Fong, Shirley S. M.; Ng, Shamay S. M.; Cheng, Yoyo T. Y.; Wong, Janet Y. H.; Yu, Esther Y. T.; Chow, Gary C. C.; Chak, Yvonne T. C.; Chan, Ivy K. Y.; Zhang, Joni; Macfarlane, Duncan; Chung, Louisa M. Y.
Abstract : Objectives . To evaluate the effects of Ving Tsun (VT) martial art training on the upper extremity muscle strength and eye-hand coordination of middle-aged and older adults. Methods . This study used a nonequivalent pretest-posttest control group design. Forty-two community-dwelling healthy adults participated in the study; 24 (mean age ± SD =68.5 ± 6.7 years) underwent VT training for 4 weeks (a supervised VT session twice a week, plus daily home practice), and 18 (mean age ± SD =72.0 ± 6.7 years) received no VT training and acted as controls. Shoulder and elbow isometric muscle strength and eye-hand coordination were evaluated using the Lafayette Manual Muscle Test System and a computerized finger-pointing test, respectively. Results . Elbow extensor peak force increased by 13.9% (P = 0.007 ) in the VT group and the time to reach peak force decreased (9.9%) differentially in the VT group compared to the control group (P = 0.033 ). For the eye-hand coordination assessment outcomes, reaction time increased by 2.9% in the VT group and decreased by 5.3% in the control group (P = 0.002 ). Conclusions . Four weeks of VT training could improve elbow extensor isometric peak force and the time to reach peak force but not eye-hand coordination in community-dwelling middle-aged and older adults.